Influence of Tooth Surface Geometry on Bending Fatigue Life of Face Gear - Yan Hongzhi; Wen Guangxu; Li Chao; Zhou Tengfei (Jixie chuandong)
Based on the coordinate transformation and meshing theory,the tooth surface equation of face gear is deduced.The finite element model of the different parameters（pressure angle,modulus）of face gear transmission is built,the influence of tooth face parameters on tooth root bending stresses,contact area and the distribution rule of bending stresses along the direction of tooth height and width are analyzed.Based on modified local stress-strain method,the fatigue crack initiation life in different roughness of grinding and milling tooth face is calculated.And the fatigue crack propagation life is predicted with damage tolerant design method.The results prove that the pressure angle has a great influence on the tooth face bending fatigue life,especially for the crack initiation life.A larger pressure angle is helpful to improve the tooth face bending fatigue comprehensive life.In addition,grinding method is more conducive to improve the tooth face bending fatigue life than milling method.This study provides a basis for the anti-fatigue design of face gear.